Sametingsvalg Tilhørighet, deltakelse, partipolitikk - Saglie, Jo; Berg-Nordlie, Mikkel; Pettersen, Torunn (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
"This book is a study of elections to the representative organ of Norway's indigenous people, the Sámi. Based on quantitative and qualitative research, the anthology examines various aspects of elections to the Sámi Parliament, both in general and regarding the 2017 election in particular. The nine chapters delve into a wide range of topics, from voter behaviour and election results to more fundamental questions regarding indigenous representation and organizing in Norway. The book covers five main themes. First, Sámi identity and criteria for voter registration. What are considered acceptable grounds for claiming to be Sámi, and what criteria do people use when judging others as Sámi or non-Sámi? When is one 'Sámi enough' to qualify for the right to vote? These questions have a bearing on the very core of Sámi politics: who should be allowed to choose representatives on behalf of the Sámi people? Second, Sámi civil society. How do organizations that represent Sámi persons and Sámi interests relate to the Sámi Parliament? Third, voter turnout. How do we explain non-voting in a system where, unlike those for other elections in Norway, one must actively register in advance to be able to vote? And what about the fact that voters in municipalities with fewer than 30 registered voters must vote in advance? Do these circumstances depress voter turnout? Fourth, the party-political landscape. What differentiates supporters of the different parties? Are there clear differences that make it easier for voters to identify the distinctions between the parties? Finally, elections and voter information. Where do voters find information about this election? We look specifically at how parties and voters find each other in South Norway, the largest constituency in the country, and yet one in which Sámi parliamentary elections are rarely covered by the media. Sámi Parliamentary Elections: Identity, Participation, Party Politics will be relevant for everyone interested in indigenous representation and participation generally, and the Sámi democratic system in Norway particularly, especially students, academics, journalists and those who are actively engaged in Sámi politics."